2018
DOI: 10.1007/s00198-018-4516-7
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture patients who experience a greater fluctuation in RDW during hospital course are at heightened risk for all-cause mortality: a prospective study with 2-year follow-up

Abstract: Hip fracture patients who experience a greater fluctuation in RDW during the hospital course are at a heightened risk for 2-year all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…[15] There are also studies in which NLR, RDW, or NHFS are emphasized for their prognostic value in predicting mortality. [5,6,13,14,24] In previous studies, NLR was significantly correlated with the one-year mortality rate following hip fractures. [27,28] In one of these studies, Forget et al [27] reported that NLR-D5 >5 was a risk factor for postoperative mortality in patients with hip fractures.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[15] There are also studies in which NLR, RDW, or NHFS are emphasized for their prognostic value in predicting mortality. [5,6,13,14,24] In previous studies, NLR was significantly correlated with the one-year mortality rate following hip fractures. [27,28] In one of these studies, Forget et al [27] reported that NLR-D5 >5 was a risk factor for postoperative mortality in patients with hip fractures.…”
Section: Discussionmentioning
confidence: 83%
“…[11,12] In a study, a correlation was reported between the increased RDW values and poor surgical outcomes or higher mortality in patients with osteoporotic fractures. [13] Thus, preoperative RDW levels may be used combined with clinical and laboratory findings to improve the risk stratification of elderly patients who are at risk for proximal femoral fractures. [14] Various risk parameters have been used to classify high-risk hip fractures in elderly patients.…”
mentioning
confidence: 99%
“…Loss of appetite in elderly patients decreases the intake of iron, folic acid, and vitamin B, which are vital to erythrocyte maturation. RDW is a prognostic factor for many diseases and can predict all causes of death [ 37 , 38 ]; however, the underlying mechanism and function in frailty warrant further research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have recently reported that RDW value is associated with adverse aging‐related nonhematologic health outcomes, especially cardiovascular diseases, mortality, and poorer outcomes in critically ill patients . It has been also reported that increased RDW value is associated with poor surgical outcomes or higher mortality rate in patients with osteoporotic fractures . However, no studies have addressed whether RDW index is associated with the future risk of hip fractures or other clinical fractures.…”
Section: Introductionmentioning
confidence: 99%